Multicultural Approach in Civics Learning in Elementary Schools - Wadawiyah, Hanifah (International Journal of Students Education, 2024)
The purpose of this study aims to assess the extent to which multicultural education has been implemented in civic education in elementary schools. Identifying the challenges and obstacles faced by teachers and students in implementing multicultural education, and finding effective solutions to overcome these problems. The type of research used in this literature review study with a literature study method that examines the implementation of multicultural education in civic learning in elementary schools. In the context of education, this approach not only improves students’ understanding of various cultural backgrounds, but also encourages attitudes of tolerance, mutual respect, and cooperation. Through an inclusive curriculum, diverse learning activities, and the use of teaching materials that reflect multiculturalism, students are invited to be actively involved in the learning process. This study shows that the application of a multicultural approach can increase learning motivation, enrich social experiences, and prepare students to face global challenges in the future. Thus, elementary schools play an important role in shaping the character of a generation that is more sensitive to differences and able to contribute positively in a diverse society.